IMPLEMENTASI STRATEGI PEMBELAJARAN TGT TERHADAP PEMBELAJAR IPAS SISTEM PENCERNAAN MANUSIA DI MI SALAFIYAH KELAS V TUMPENG - Ahmad Muzaky Syamsuddin; Muhammad Suwignyo Prayogo; Muhammad Nizam Bayhaqi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the application of TGT (Teams Games Tournaments) cooperative learning on IPAS learning outcomes about the human digestive system at MI Salafiyah Tumpeng to increase student activity and learning motivation. TGT was applied in grade 5 by involving students in fun group-based learning through tournaments or educational games. The learning began with ice-breaking activities to attract students' attention, followed by group division and presentation of material on the human digestive system, as well as group discussions. After that, a tournament was held to test students' understanding through questions that were answered in turns between groups. IPAS learning using the TGT learning strategy proved to be able to create an active and enjoyable learning atmosphere, increase student participation in each activity, and build cooperation between groups. Although there were challenges in managing students with attention and speech disorders, the use of clear instructions, jargon, and competition-based games was effective in maintaining student focus and motivation. The results of the observation showed that the application of TGT succeeded in increasing student activity and motivation to learn, which was reflected in their enthusiasm during learning and more productive group discussion results. Thus, IPAS learning using the cooperative learning system type TGT can be used as an effective method to improve the quality of learning at MI Salafiyah.Keywords: keyword 1, keyword 2, keyword 3